Effect of an interdisciplinary intervention with motivational approach on exercise capacity in obese adolescents: a randomized controlled clinical trial - Zanatta,Letiane Bueno (2020)
ABSTRACT Objective To evaluate the effect of an interdisciplinary intervention with a motivational approach on exercise capacity and usual physical activity levels in overweight and obese adolescents. Methods This is a randomized, controlled clinical trial with single blinding of subjects. Adolescents aged 15 to 18 years with overweight and obesity (body mass index ≥ 85 percentile) were included. The adolescents were randomized into two groups: interdisciplinary intervention or control − traditional approach aiming at lifestyle modifications. The initial evaluations were carried out, including the cardiopulmonary exercise test and the physical activity level measurement by using the International Physical Activity Questionnaire and a pedometer. The evaluations were performed in two moments: time zero (time of inclusion in the study) and after 3 months (end of intervention). There were 12 sessions with weekly meetings. Results A total of 37 participants were included, 19 in the Intervention Group. There were no significant differences in the baseline demographic, anthropometric and physical activity characteristics between groups, with mean age of 17.3±1.0 years in the Control Group, and 16.8±0.9 years in the Intervention Group (p=0.14). The motivational intervention did not cause significant differences (p>0.05) in the comparison of the variables of exercise capacity and usual physical activity (questionnaire and pedometer) between groups. Conclusion The intervention with a motivational approach did not alter exercise capacity and levels of usual physical activity in overweight and obese adolescents. Clinical Trial Registry: NCT02455973 and REBEC: RBR-234nb5.